CD47 Deficiency in Mice Exacerbates Chronic Fatty Diet-Induced Steatohepatitis Through Its Role in Regulating Hepatic Inflammation and Lipid Metabolism - Tao, Hui-Chao; Chen, Ke-Xin; Wang, Xue; Chen, Bo; Zhao, Wai-Ou; Zheng, Yang; Yang, Yong-Guang (Frontiers in Immunology, 2020)
Inflammation is one of the hallmarks of nonalcoholic steatohepatitis. CD47 is a widely expressed transmembrane protein that signals through inhibitory receptor SIRPα to inhibit macrophage activation and phagocytosis. In this study, we sought to investigate the role of CD47 in hepatosteatosis and fibrosis induced by a chronic high fat diet (HFD), by comparing disease development in wild-type (WT) and CD47KO mice fed HFD for 40 weeks. The HFD induced remarkably more severe hepatic steatosis and fibrosis, but less body weight gain and less subcutaneous fat accumulation in CD47KO mice compared to WT mice. Liver tissues from HFD-fed CD47KO mice exhibited enhanced inflammation characterized by increased proinflammatory cytokine production and increased NF-κB activation compared to similarly fed WT mice. Although higher expression of apolipoproteins was observed in CD47KO mice compared to WT mice under low fat diet (LFD), HFD-fed WT and CD47KO mice showed comparably prominent downregulation of these apolipoprotein genes, suggesting that the marked difference observed in lipid accumulation and hepatosteatosis between these mice cannot be explained by changes in apolipoproteins. Like apolipoproteins, SIRT1 and PPARα, which are involved in regulation of both lipid metabolism and inflammation, were more highly expressed in CD47KO than WT mice under LFD, but more severely suppressed in CD47KO than in WT mice under HFD. Taken together, our results indicate that CD47 plays a significant role in the pathogenesis of HFD-induced hepatosteatosis and fibrosis through its role in regulation of inflammation and lipid metabolism.